A Silesian perspective on small and medium-sized enterprises facing the challenges of the green economy - Helena Tendera-Właszczuk; Aldona Frączkiewicz-Wronka; Sylwia Słupik; Damian Łukasik (International Entrepreneurship Review)
Objective: This article aims to identify and analyse the opinions of small and medium-sized enterprises (SME) entrepreneurs operating in the Silesian Voivodeship on the prospects of their companies in relation to the need to implement so-called green solutions. The key aim of the study was to identify differences in assessments of future developments in the labour market of the Silesian Voivodeship between two groups of respondents: SME companies with the potential to create green jobs and SMEs in the green sector.